Rural EFL Teacher’s Challenges in Improving Students’ Higher Order Thinking Skills - Pasutri, Novita Silta; Yeni, Melda (STAI Auliaurrasyidin Tembilahan, 2022)
This research aims to explore the rural EFL teacher’s challenges in improving students’ higher order thinking skills. The participant of this research was one English teacher who teach in the Junior High School in Gaung district. By using qualitative approach, the researchers collected the data employs non-participant observation in the teaching and learning process, interviewed the English teacher, and took documents by collecting the lesson plan. The result of this research showed that the challenges in teaching higher-order thinking skills in the rural area are the teacher’s knowledge and ability to teaching for HOTS is still low, passive students, students’ low English proficiency, the limitation of the school facility, and lack of sources. Based on the finding above, this research recommends to the school to give a facility or train the teachers about how to teach the students’ higher-order thinking skills based on the demand of 2013 Curriculum. Besides that, the development of HOTS in the rural area is not easy for the teachers because of all those challenges. So, the headmaster or the education authorities should find the solution to make all the students in the rural area can reach the expectation of the Higher Order Thinking based on 2013 curriculum.